Inverse Relationship: Social Integration and Persistence in an Introductory Psychology Course for Secondary Students - Forbes, Sean; Robichaux-Davis, Rebecca; Smith, Wade; Bruder, Emese; Unal, Hakan; Guarino, A. J. (Advances in Social Sciences Research Journal, 2018)
The researchers investigated the relationship between social integration and persistence for high school students enrolled in an introductory psychology course. The researchers hypothesized that the social system interfered with the academic mission of the high school in this study. Persistence was operationalized as completion of an introductory psychology course with a grade of D or higher. Participants were 241 high school students in the southeastern United States. In support of the researchers’ initial expectations, students scoring higher on social integration were more likely to dropout. Based on the results of this investigation, secondary teachers should take a more active role in promoting interactions with their students. By employing a more collaborative learning environment, students may become more involved socially and academically. This could subsequently aid in reducing the high rate of attrition.